How to support recovery phase for landslide through livelihoods? case study: Kulon Progo Regency, Indonesia - Setyawati Dewanti Diah; Jaenul Haq Jejen; Viviani Nurhanifah Nita; Bi Chuanchen (E3S Web of Conferences)
The global climate is increasingly responsible for the frequency of extreme weather events, which have significant implications for vulnerable biological systems. Among these events, rainfall-induced landslides are recognized as one of the most severe geological disasters, particularly in Indonesia. The recovery phase is often the weakest link in disaster management implementation. This study aims to discern and assess the effects of the recovery phase on livelihoods in Kulon Progo, Indonesia, following landslides. The study examines the impact of human, social, physical, natural, and financial capital, as well as transformations in structure and process (TSP), on the recovery phase. The unit of analysis is households, with data collected from 300 households through stratified random sampling. Path analysis was applied to achieve the study’s objectives. The findings reveal that human capital (0.376**), social capital (0.279***), physical capital (0.182*), and TSP (0.263***) have a direct effect on the recovery phase. Additionally, social capital (0.352***) and physical capital (0.180**) indirectly influence the recovery phase through TSP as a mediator. To strengthen the recovery phase in landslide disaster management, the study identifies seven activities that directly support the recovery phase and another seven that indirectly contribute to its reinforcement.